Students' perception towards learning and teaching of the KBSM English literature component: a case study /Hamizah Hasbullah - Hasbullah, Hamizah (2014)
This research aimed to investigate Form 4 students' perception towards the KBSM English Literature Component as well as the challenges that they face in learning the literature component. It also looked into the teachers' strategies in teaching the literature component and the problems that they face in teaching the KBSM English Literature Components. This research involved sixty Form 4 students and six English teachers from SMK Abu Bakar, Temerloh, Pahang. The data was collected through two questionnaires; questionnaire for students and questionnaire for teachers. Results showed that the Form 4 students had positive perception towards the KBSM English Literature Component. They were aware of the benefits of learning literature and literature has helped them in improving their language proficiency. Even though the students were in favour of learning literature component, it was shown in the data that the students face three main challenges which were lack of proficiency in English Language, lack of background knowledge and lack of time. Findings from the teachers' responses revealed that the teachers' teaching strategies and methods were inclined towards teacher centred. Based on the results, teachers faced two major problems in teaching the KBSM English Literature Component which were insufficient teaching time and students' lack of reading habit. It is hoped that this study will motivate teachers to improve their teaching of the literature component and to ensure that the students gain more benefits from learning literature.